Secretory carcinoma arising in radial scars of the breast: A case report and review of literature - Menon Santosh; Shet Tanuja; Munshi Anusheel; Badwe Rajendra (Wolters Kluwer Medknow Publications, 2009)
Radial scars or complex sclerosing lesions are common benign lesions in the breast with characteristic radiological and pathological features. The pathological diagnosis of carcinoma arising in this setting requires careful amalgamation of clinical, radiological and morphological details. Ancillary techniques like immunohistochemistry aid in the diagnosis. We report an unusual case of a secretory carcinoma arising in the background of a radial scar.